Periodontal status among relatives of aggressive periodontitis patients and reliability of family history report - M. A. Llorente (Blackwell Synergy, 2006)
Objectives: To assess the periodontal status of relatives of Aggressive Periodontitis (AgP) patients, and to evaluate the reliability of the family history report as provided by the proband. Material and Methods: Data from 54 AgP patients were gathered along with a family history report for each of their relatives. Only 27 patients (probands) had relatives willing to be examined. This yielded a total of 61 relatives from whom the periodontal status was obtained. The family history report for each examined relative was compared with the periodontal diagnosis made at examination to assess reliability. Results: Eight percentage of the examined relatives, aged between 12–76, were diagnosed with AgP, while chronic periodontitis was present in 39%, gingivitis in 38% and 15% were healthy. If the report provided by the proband was positive, the likelihood of finding any type of periodontitis in that relative was 85.7%, whereas if the report was negative the likelihood of the absence of periodontitis was 70.6%. Conclusion: The percentage of examined relatives who were affected with AgP (8%), although lower than percentages reported in other AgP family studies, was still higher than the prevalence of the condition in random populations. Reliability of periodontal family history was considered good and more reliable when it was positive.